SCHUMPETERIAN GROWTH THEORY: EMPIRICAL TESTING OF BARRIERS TO COMPETITION-PROXIMITY TO FRONTIER ALGORITHM - Petrović, Predrag; Nikolić, Goran (Economic Annals, 2018)
This study is dedicated to empirical testing of barriers to competition effect on productivity growth, taking into account the hypothesis that different policies improve economic growth in countries at different levels of technological development. The results of econometric analysis of two panel data sets comprising 144 countries (not controlled for education) and 128 countries (controlled for education) have demonstrated that when approaching the technology frontier, countries with high barriers to competition lose their productivity growth much faster than countries with a low barrier, which is the direct result of the decreasing but positive influence of barriers to competition on productivity growth, regardless of whether the economy is underdeveloped or advanced. This positive effect of barriers can be rationalized by Romer’s (1990) product variety model; or possibly by the inverted-U pattern between competition and innovation proved by Aghion et al. (2005), under the assumption that these sample countries are on the downward slope. Finally, the positive effect of barriers, irrespective of the degree of the countries’ technological development, implies that the theory is not completely consistent with empirical data.